Quantitative sensory phenotyping in chronic neuropathic pain patients treated with unilateral L4-dorsal root ganglion stimulation - Kinfe, Thomas M.; Willebrand, Nico von; Stadlbauer, Andreas; Buchfelder, Michael; Yearwood, Thomas L.; Muhammad, Sajjad; Chaudhry, Shafqat R.; Gravius, Sascha; Randau, Thomas; Winder, Klemens; Maihöfner, Christian; Gravius, Nadine; et al. (Journal of translational medicine, 2020)
In a previous study, we reported that selective dorsal root ganglion stimulation (DRGSTIM) at DRG level L4 promoted a favorable outcome for complex regional pain syndrome (CRPS) patients along with DRGSTIM-related changes of inflammatory biomarkers in blood and saliva. The impact on somatosensation is largely unknown. Herein, we assessed the quantitative sensory profile to quantify L4-DRGSTIM effects in CRPS patients.